Characterization of unusual MgCa particles involved in the formation of foraminifera shells using a novel quantitative cryo SEM/EDS protocol. (1st September 2018) - Mor Khalifa, Gal; Kahil, Keren; Erez, Jonathan; Kaplan Ashiri, Ifat; Shimoni, Eyal; Pinkas, Iddo; Addadi, Lia; Weiner, Steve
Graphical abstract: Abstract: Quantifying ion concentrations and mapping their intracellular distributions at high resolution can provide much insight into the formation of biomaterials. The key to achieving this goal is cryo-fixation, where the biological materials, tissues and associated solutions are rapidly frozen and preserved in a vitreous state. We developed a correlative cryo-Scanning Electron Microscopy (SEM)/Energy Dispersive Spectroscopy (EDS) protocol that provides quantitative elemental analysis correlated with spatial imaging of cryo-immobilized specimens. We report the accuracy and sensitivity of the cryo-EDS method, as well as insights we derive on biomineralization pathways in a foraminifer. Foraminifera are marine protozoans that produce Mg-containing calcitic shells and are major calcifying organisms in the oceans. We use the cryo-SEM/EDS correlative method to characterize unusual Mg and Ca-rich particles in the cytoplasm of a benthic foraminifer. The Mg/Ca ratio of these particles is consistently lower than that of seawater, the source solution for these ions. We infer that these particles are involved in Ca ion supply to the shell. We document the internal structure of the MgCa particles, which in some cases include a separate Si rich core phase. This approach to mapping ion distribution in cryo-preserved specimens may have broad applications to other mineralized biomaterials. Statement of significance: Ions are an integral part of life, and some ions play fundamental roles in cell metabolism. Determining the concentrations of ions in cells and between cells, as well as their distributions at high resolution can provide valuable insights into ion uptake, storage, functions and the formation of biomaterials. Here we present a new cryo-SEM/EDS protocol that allows the mapping of different ion distributions in solutions and biological samples that have been cryo-preserved. We demonstrate the value of this novel approach by characterizing a novel biogenic mineral phase rich in Mg found in foraminifera, single celled marine organisms. This method has wide applicability in biology, and especially in understanding the formation and function of mineral-containing hard tissues.